PENGARUH ROUNDUP TERHADAP POPULASI SERANGGA TANAH KECAMATAN MAULAFA NUSA TENGGARA TIMUR - Xaveria Christin Angelic Kaza; Mario J. Santrum; Paulus Taek (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Soil fauna is an important component of the soil ecosystem, playing a role in the decomposition of organic matter, nutrient cycling, and improving the physical, chemical, and biological properties of the soil. The use of Roundup herbicide as a weed control is suspected to have an impact on the presence and diversity of soil fauna. This study aims to determine the composition of soil fauna, the level of similarity, and the diversity index of soil fauna in land sprayed with Roundup herbicide and control land. The study was conducted in Maulafa District, Kupang City, using survey and field experiment methods. Soil fauna samples were taken at depths of 5, 10, and 15 cm and from the soil surface using a zigzag technique, then extracted with a modified Tullgren funnel. Environmental parameters measured included soil temperature, soil pH, and soil moisture. Data were analyzed using the similarity index, the Shannon-Wiener diversity index (H’), and the soil fauna dominance index. The results showed that the application of Roundup herbicide did not cause mass lethality to soil fauna. The soil fauna composition in the treatment area remained diverse and was dominated by the order Collembola, particularly the families Isotomidae, Sminthuridae, and Onychiuridae. The similarity level between the treatment and control areas was high, with relatively stable diversity index values. This condition was influenced by the moist, litter-covered soil microclimate and the adaptability of the soil fauna through the detoxification mechanism of the Mixed Function Oxydases (MFO) enzyme.